Optimizing Swarm UAV Scheduling for Efficiency in Complex Operations and Collision Avoidance: Optimized Scheduling Strategies for Swarm UAVs in High-Density Airspace - Raharja, Annisa Amalia (AI Society & STMIK Indonesia, 2024)
The use of drones or Unmanned Aerial Vehicle (UAVs) has rapidly evolved across various civil, public, and military applications over the past two decades. Military UAVs have long been used for border surveillance, while civilian UAVs can monitor traffic, provide disaster alerts, and deliver medical supplies. Swarm UAVs, inspired by natural animal colonies such as birds and bees, enable complex flight coordination in disaster situations. To optimize operations, the implementation of scheduling methods for swarm drones is crucial. This method involves scheduling flights based on mission priorities, estimated time of arrival, and drone battery conditions. Effective scheduling ensures operational efficiency and flight safety of drones.